Reflection of Interaction of Field Work Lecture (KKN) Students of UIN Walisongo Semarang with the Putatagede Community through the Dynamics of the Farewell Event - Achmad Dahlan; Nityasa Respati Pratidina; Wafi Fajar Ramadhan; Fitria Susilowati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This qualitative case study explores the dynamics and reflections arising from the interaction between Kuliah Kerja Nyata students from Post 82, UIN Walisongo Semarang, and the Putatgede community, focusing on their farewell event. Data was collected through participant observation, semi-structured interviews with students and community members, and document analysis. Findings reveal the farewell event as a microcosm of the KKN experience, highlighting themes of reciprocal learning, cultural exchange, emotional connection, and challenges faced. The event fostered a sense of community ownership and sustainability of initiatives. This study underscores the importance of culminating events in fieldwork programs for reflection, celebration, and strengthening community ties.